Congestion management through topological corrections: A case study of Central Western Europe. (November 2015) - Han, Jinil; Papavasiliou, Anthony
Abstract: The integration of an increasing amount of renewable generation within Europe is posing operational challenges that require various balancing actions. System operators therefore need to rely increasingly on the active control of the transmission network. Transmission topology control is a fast and economical option to add flexibility to the transmission system. We model the current methodology for controlling congestion in the Central Western European (CWE) market and quantify the benefits of topology control. We also compare the results with a nodal pricing model. Our computational results suggest that topology control can significantly reduce congestion management costs under the current market coupling regime whereas the benefits of topology control are limited under nodal pricing. Topology control emerges as an attractive and implementable means of managing congestion as it provides a significant percentage of the cost savings that would be achieved by overhauling the existing European market design and shifting to a nodal pricing regime. Abstract : Highlights: We present the congestion management model in the CWE region. The benefits of topology control in the CWE region are quantified. Topology control significantly reduce congestion under the current market coupling. The benefits of topology control are limited under the nodal pricing regime. Network topology control is a promising option for mitigating congestion in Europe.